Introduction to action research : Social research for social change - Greenwood, Davydd J.; Levin, Morten (Thousand Oaks : London : New Delhi : SAGE Publications, 1998)
Introduction to Action Research presents a strong case for action research to be regarded as a form of scientific inquiry of greater validity than the more mainstream forms of social science research.
Includes references and index.
Keywords: action research